Terminology of fruit set and fruit drop of sour cherry cultivars - Davarynejad, G. H.; Nyéki, J.; Tornyai, J.; Szabó, Z.; Soltész, M. (International Journal of Horticultural Science, 2009)
Fruit set and fruit drop rates of 9 sour cherry cultivars (‘Érdi bôtermő’, ‘Debreceni bőtermő’, ‘Kántorjánosi’, ‘Újfehértói fürtös’, ‘Éva’, ‘Petri’ ‘Oblocsinszka’, ‘Pandy 279’ and ‘Csengôdi’) of eight years-old trees grown in Újfehértó, located in the Eastern north part of Hungary which grafted on Prunns mahaleb have been studied. Significant differences have been found in fruit set among cultivars. The average percentage of fruit set was 18.3%, which the ‘Oblacsinszka’ by 32.6% the highest fruit set, while ‘Debreceni bőtermő’ is very similar to ‘Pandy279’ showed lowest (12%) fruit set. Seasonal changes of fruit set and drop shows that there are four abscission peaks. The first fruit abortion wave appears during second week after pollination Thereafter, the second and third dropping period was found during the third and forth weeks after pollination. The forth abscission happened on the forth week after pollination. The highest fruit drop happened on ‘Pandy279’ (92.4%) very similar to ‘Éva’ (90%) while the lowest fruit drop observed in ‘Oblocsinszka’ (71.5%)